Distribution pattern and molecular signature of cholinergic tuft cells in human gastro-intestinal and pancreatic-biliary tract - Schütz, Burkhard; Strobel, Oliver; Büchler, Markus W. (Scientific reports, 2019)
Despite considerable recent insight into the molecular phenotypes and type 2 innate immune functions of tuft cells in rodents, there is sparse knowledge about the region-specific presence and molecular phenotypes of tuft cells in the human digestive tract. Here, we traced cholinergic tuft cells throughout the human alimentary tract with immunohistochemistry and deciphered their region-specific distribution and biomolecule coexistence patterns. While absent from the human stomach, cholinergic tuft cells localized to villi and crypts in the small and large intestines. In the biliary tract, they were present in the epithelium of extra-hepatic peribiliary glands, but not observed in the epithelia of the gall bladder and the common duct of the biliary tract. In the pancreas, solitary cholinergic tuft cells were frequently observed in the epithelia of small and medium-size intra- and inter-lobular ducts, while they were absent from acinar cells and from the main pancreatic duct. Double immunofluorescence revealed co-expression of choline acetyltransferase with structural (cytokeratin 18, villin, advillin) tuft cell markers and eicosanoid signaling (cyclooxygenase 1, hematopoietic prostaglandin D synthase, 5-lipoxygenase activating protein) biomolecules. Our results indicate that region-specific cholinergic signaling of tuft cells plays a role in mucosal immunity in health and disease, especially in infection and cancer.
Gesehen am 14.01.2020